Translation Equivalence Degrees among Indonesian EFL Undergraduate Students - Baihaqi, Akhmad (Buletin Al-Turas, 2024)
PurposeThe way to produce an equivalent translation text appears hard that every translation work should engage with diverse language and cultural systems. The issues are expected to affect both translation students and professional translators. Therefore, this current work aims to discover in-depth information about translation equivalence degrees among Indonesian EFL undergraduate students.MethodThis study employed qualitative content analysis. The research data included documentation of the translation texts from English into the Indonesian language, which resulted in 22 students majoring in English education at a public university in Banten Province, Indonesia. The source language texts were derived from the news-item texts published in national newspapers. The data analysis procedure comprised comparing the two texts, classifying, discussing, drawing conclusions, and making interpretations. Results/findingsThe study of the translation texts revealed that 11 texts (50%) referred to near-optimal translation, six texts (27%) to partial translation, and five texts (23%) to poor translation.ConclusionGiven that none of the students' translation outputs achieved the optimal equivalency; this conclusion suggests that students' translation knowledge and skills still need to be improved by regular practice and discussion at each translation course meeting.